(3CMcGe GdTjc eOfjG hLfGFjGs - (3eMeO eMehO(B, (3GdeUQjs ((3GdGScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2005)
(3fXQI YGeI aj CMcGe GdTjc aj eUQ hGdHdGO GdYQHjI(B- (3CMcGe GdTjc aj GdbGfhf GdJLGQj GdeUQj(B- (3YedjGJ GdHfhc ef GdhGLgI GdbGfhfjI HGdfSHI ddTjc(B-(3CMcGe eMceI GdfbU aj GdTjc(B- (3LQjeI EYWGA GdTjc HOhf QUjO aj GdJTQjY GdShOGfj(B- (3LQjeI EYWGA GdTjc HOhf QUjO aj GdJTQjY GdeUQj(B- (3CMcGe eMceI fbU GdOGFQI GdLfGFjI aj GdTjcs
Keywords: (3GdTjcGJs; (3LQGFe GdCehGds